Impact of Solution-Focused Brief Counseling in Reducing Social Anxiety of College Student Victims of Bullying - Hengky Yandri; Firman Firman; Afdal Afdal (UIN Siber Syekh Nurjati Cirebon, 2023)
Research shows that Bullying is one of the problems experienced by individuals in many countries, including Indonesia. In this study, cases were discussed in college; we intervened with clients who were victims of Bullying to reduce their anxiety by using the Solution-Focused Brief Counseling approach. This study is a type of case report that presents a case report of a client who is a victim of Bullying. This client is 20 years old and is a college student at college X. Data is revealed through counselling interviews and analyzed using the success assessment of Solution-Focused Brief Counseling. The findings reveal that clients experience anxiety after being bullied by their seniors at welcoming freshman activities. After the counselling process, clients feel relieved and calm without excessive anxiety. This proves that clients benefit from the counselling process with the Solution-Focused Brief Counseling approach that has been carried out. Researchers should then try the Solution-Focused Brief Counseling approach with different problems.